Hybrid education: an alternative for the inclusive education of the deaf (Research, Society and Development, 2019)
Information and communication technology are an effective means that have been applied in education because it allows teachers to work with early stimulation of students with disabilities, aiming to promote the proper development of these students. In the face of this, the objective of this study is to present the contributions of hybrid teaching to the teaching and learning process of students, especially deaf students. For the development of this study, the qualitative approach was adopted, with bibliographic research. The study concludes that hybrid teaching presents a diversity of methods to be applied in the inclusive education of the deaf, allowing a transdisciplinary approach a good reflection on the contemporary context in education, provided that it is used properly, with due planning, combining with several technological resources, but for its implementation it is necessary that a cultural reelaboration occurs, mainly the traditional method of teaching that is still rooted in our culture.